600. TREATMENT OUTCOME OF CLINICALLY UNRESECTABLE ESOPHAGEAL CANCER AFTER NEO-ADJUVANT CHEMOTHERAPY WITH DOCETAXEL, CISPLATIN AND 5-FLUOROURACIL. (24th September 2022) - Chan, Wing Lok; Wong, Ian YH; Choi, Horace Cheuk-Wai; Tsang, Terence; Lam, Adrian; Tse, Rosa; Zhang, Riki; Chan, KK; Wong, Claudia; Law, Betty; Lam, Ka-On; Chan, Fion; et al.
Abstract: Standard therapy for locally advanced unresectable esophageal cancer is neoadjuvant chemotherapy followed by definitive chemoradiotherapy (CRT). However, the prognosis was modest with the mean survival being around 1 year. Emerging evidence shows the efficacy results of using neo-adjuvant chemotherapy docetaxel-cisplatin-5FU (DCF) for locally advanced esophageal tumor. We reviewed the long-term clinical outcomes and safety data of neo-adjuvant chemotherapy DCF and subsequent definitive treatment in locally advanced clinically unresectable esophageal cancer. All patients with locally advanced clinically unresectable esophageal cancer without any distant metastases and received induction DCF (docetaxel 70 mg/ m2 D1, cisplatin 70  mg/ m2 D1, 5-fluorouracil 750  mg/ m2 on D1-5 Q3 weeks for 3 cycles) with an aim for conversion to definitive surgery or CRT were included. Primary outcomes were overall survival (OS) and conversion rate (from unresectable to resectable tumor after DCF). Secondary outcomes include relapse pattern, safety data of chemotherapy and post-op complications. Total 47 patients (median age 62yo, male: 41 (87.2%)) received neo-adjuvant DCF. 24 patients (41.4%) had subsequent surgery and 7 (14.9%) had definitive CRT. The median OS was significantly longer in the surgical group than CRT group (40.2 vs. 9.1months, HR 3.33, 95%CI 1.22–9.07, p=0.02) and no definitive treatment (40.2 vs. 6.3months, HR 8.51, 95%CI 3.7–19.73, p<0.001). Patients with surgery had a lower risk of local relapse (100% vs. 33%, p<0.001) but comparable risk of distant metastasis (47.8% vs. 58.6%, p=0.538) than those without surgery. The incidence of G3/4 adverse events of DCF was 44.7%. 11 patients had post-op complications. Neo-adjuvant chemotherapy with DCF and subsequent conversion surgery offered a chance of cure with long-term survival benefit and manageable toxicities in patients with locally advanced unresectable esophageal cancer.